2015
DOI: 10.1179/1743284714y.0000000679
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermal and electrical properties of plasticised PVA based polymer electrolyte

Abstract: Polymer electrolyte films of polyvinyl alcohol as host polymer, poly(3,4-etylenedioxythiophene)/poly(styrenesulphonate), magnesium bromide were prepared using solution cast technique. Succinonitrile was used as plasticiser in the matrix at different concentrations. These films were characterised using thermogravimetric analysis, X-ray diffraction and ac impedance spectroscopy. The conductivity measurement was used to determine the ionic conductivity of the polymer electrolyte at different temperature and frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…The maximum DC conductivity measured for the current study is found to be 4.5 × 10 −6 S/cm and greater than those reported for PVA:Mg(NO 3 ) 2 and PVA:KCl, which are 7.36 × 10 −7 S/cm and 9.68 × 10 −7 S/cm, respectively [ 1 , 15 ]. However, it is very close to the obtained value reported by Sheha et al [ 14 ], in which the highest conductivity was 9.8 × 10 −6 S/cm for PVA, PEDOT:PSS-MgBr 2 system.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The maximum DC conductivity measured for the current study is found to be 4.5 × 10 −6 S/cm and greater than those reported for PVA:Mg(NO 3 ) 2 and PVA:KCl, which are 7.36 × 10 −7 S/cm and 9.68 × 10 −7 S/cm, respectively [ 1 , 15 ]. However, it is very close to the obtained value reported by Sheha et al [ 14 ], in which the highest conductivity was 9.8 × 10 −6 S/cm for PVA, PEDOT:PSS-MgBr 2 system.…”
Section: Resultssupporting
confidence: 91%
“…However, the main drawbacks of using PEO in the preparation of polymer electrolytes are its strong affinity to crystallize and its low ionic conductivity [3]. The literature reviews revealed that most researchers focused on other types of polymers, such as chitosan [4,5,6,7,8,9], methyl cellulose [10,11,12,13,14] and poly(vinyl alcohol) [1,2,3,14,15,16]. Polyvinyl alcohol (PVA) polymer is widely used in electrochemical and electrochromic devices due to its bio-compatibility and superior mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheha and colleagues also demonstrated a GPE complex with moderate ionic conductivity above 10 −4 S cm −1 using PVA/poly (3,4-etylenedioxythiophene): poly(styrenesulphonate) (PEDOT:PSS)-based GPE with MgBr 2 and SN as a plasticizer. 139 Mg ion conduction was observed from the transference number of 0.28 and stable, low capacity charge/ discharge cycling of a Mg|V 2 O 5 cell over 40 cycles. The electrodes were not fully utilized with SEM-EDS showing minimal change in Mg content (0.93 → 2.55 wt%) in the cathode after discharge.…”
Section: Gel Polymer Electrolytes (Gpes)mentioning
confidence: 93%
“…A polymer electrolyte based on poly (vinyl alcohol) (PVA) and poly(3,4-Etylenedioxythiophene):poly(styrenesulfonate) (PEDOT: PSS) complexed with magnesium bromide (MgBr 2 ) was synthesized and the maximum conductivity of 9.89×10 −6 S cm −1 was found for the optimum polymer composite film with 30 wt% MgBr 2 at room temperature [7]. The work was extended to optimize the ionic conductivity via doping the optimized polymer electrolyte by succinonitrile (SN) and the ionic conductivity increased from 9.8×10 −6 to 2.83×10 −4 S cm −1 for 20 wt% SN [9]. The highest recorded ionic conductivity of the PE film based 70 wt% PVA, 30 wt% MgBr 2 and 1 wt% TEGDME was 1.3×10 −6 S.cm −1 [10].…”
Section: Introductionmentioning
confidence: 99%